Інформування контрагента про односторонню відмову від договору - Чалий, Ю. І.; Chalyi, Yu. I.; Юрій Чалий (Вісник Харківського національного університету внутрішніх справ. – 2023. – № 4 (103). - С. 91-106, 2023)
Зазначено, що чинне цивільне законодавство характеризується певною неповнотою, що не дозволяє говорити про наявність послідовного правового режиму щодо інформування ініціатором односторонньої відмови від договору про цей факт свого контрагента. Наголошено на необхідності диференціації законодавчих правил про визначення форми та порядку інформування заінтересованої сторони про односторонню відмову від договору іншою стороною. Критеріями такої диференціації є суб’єктний склад, вид договірних відносин, а також мотиви відмови. Запропоновано внести зміни до норм про відмову від правочинів, де мають міститися найбільш загальні положення про здійснення поінформованої односторонньої відмови від договору.

The study focuses on the issue of notification of the initiator of unilateral withdrawal from a contract to its counterparty of such withdrawal. In particular, the problematic issues of de-termining the form and procedure for such notification and establishing the time when an agreement unilaterally withdrawn by one of its parties will be considered amended or termi-nated are considered. Current civil law does not provide clear answers to these questions. The necessity of differentiating the legislative rules which will determine the procedure for inform-ing the interested party of the unilateral withdrawal from a contract by the other party, and also establish the moment when the legal consequences caused by unilateral withdrawal from a contract come into force, is pointed out. The criteria for such differentiation are the subject matter and type of contractual relationship, as well as the reasons for withdrawal from the contract, i.e. whether it arose due to a breach of contract by the counterparty or is related to other reasons. When the withdrawal is caused by a breach of contract, the injured party gen-erally does not have to notify the offending party in advance of its intention to unilaterally withdraw from the contract. It is acceptable to give notice after the fact, but with the obligatory immediate notification of the offender or within another reasonable time. In the case of with-drawal for other reasons, the initiator of the withdrawal must usually inform its counterparty in ad vance. In the latter case, the notice of withdrawal has the form of a warning in the proper sense of the word. It is noted that, as a general rule, a withdrawal must be made in the same form as the contract that is being withdrawn by one of its parties. In the first case of withdrawal, i.e. when it is caused by an offence, legal consequences may arise with the first acts of defensive action taken by the injured party. There may be situations where legal consequences of this type of waiver arise from the moment the offending party receives the notice. In the second case of withdrawal - "for other reasons" - the legal consequences of the withdrawal will appear not earlier than the moment when the interested party is informed of the unilateral withdrawal from the contract by its counterparty. It is proposed to amend the rules on withdrawal from transactions, which should contain the most general provisions on the implementation of informed unilateral withdrawal from a contract.

Отмечено, что действующее гражданское законодательство характеризуется определенной неполнотой, что не позволяет говорить о наличии последовательного правового режима информирования инициатором одностороннего отказа от договора об этом факте своего контрагента. Подчеркнута необходимость дифференциации законодательных правил об определении формы и порядка информирования заинтересованной стороны об одностороннем отказе от договора другой стороной. Критериями такой дифференциации есть субъектный состав, вид договорных отношений, а также мотивы отказа. Предложено внести изменения в нормы об отказе от сделок, где должны содержаться наиболее общие положения об осуществлении информированного одностороннего отказа от договора.
Notification of the counterparty of unilateral withdrawal from the agreement
Keywords: одностороння відмова від договору; unilateral withdrawal from the contract; односторонний отказ от договора; інформування; informing; информирование; контрагент; counterparty; припинення договірних зобов’язань; termination of contractual obligations; прекращение договорных обязательств; цивільне законодавство; civil legislation; гражданское законодательство